Dinâmica de operadores lineares em espaços de Fréchet - Braz, José Henrique Souza (2017)
In this work we study the notion of hypercyclicity, which is the main phenomenon studied in linear dynamics of operators. We will investigate the notions of mixing and weakly mixing operators that under certain hypotheses are hypercyclic. We will also show some criteria to obtain hypercyclicity and finally we will prove that in any separable infinite dimensional Fréchet space it is possible to define an operator that is hypercyclic.